Effect of sedation propofol with target controlled infusion on cognitive functions on patients undergoing operative procedures under local anaesthesia in hospital universiti sains malaysia - Hasan, Khathija (2011)
Introduction: Surgical procedures are increasingly being performed under local anaesthesia alone but most patients prefer to be sedated. Sedation combined with local anaesthesia is a safe alternative to GA as spontaneous respiration, protective reflexes and patient co operation are retained while fear and apprehensions are reduced. The changes in cognitive function frequently complicate the post operative course of patients undergoing non cardiac surgery. Some patients are at a greater risk than others of cognitive impairment and what doses of drugs? and if yes then for how long? Hence, the need for experimental study to answer these questions. Objectives: The aim of this study was to evaluate the cognitive changes after propofol sedation via TCI as monitored anesthetic care and factors influencing it were explored. Methodology: This was a prospective randomized controlled trial. Study subjects were placed in either arm as per double block randomization preoperative after fulfilling inclusion criteria. Standard monitoring was done during intraop and postoperative period. One hundred and four consenting ASA physical status I and II patients scheduled to undergo elective surgical procedures with local infilteration were assigned, to receive either sedation propofol infusion or only local infiltration (without propofol sedation) intraoperatively, by the researcher. Upon arrival in preoperative holding area, patients were to undergo two cognitive function tests (MMSE, SOMCT) beside the demographic data as baseline. These tests were carried out by blinded investigator to avoid bias. The patients were then taken into operating rooms and standard monitoring was applied. After intravenous line was secured, local infiltration of operative area was done by surgeon. Interventional group received sedation propofol via marsh model target control infusion targeting plasma concentration level of 0.5ug/ml, and those in control group received local infiltration only. Propofol infusion was stopped at the end of surgery. And patients were brought to post anaesthetic care unit (PACU) and monitored continuously. Cognitive function tests were repeated at 20 and 60 minutes postoperatively for both the groups by blinded investigator. Standard clinical discharge criteria were used to discharge patients from recovery room. Results: Demographic data were comparable in both the groups. Cognitive status was improved, at the end of 60 minutes in both the study groups but slower response was observed in experimental group as compared to control group. Analysis of co variable demonstrated that males showed more marked cognitive decline as compared to females in the experimental group, whereas males of control group had no observed cognitive drop. Similar changes were observed with other co variables like race, age, smoking habits and subjects with history of previous general anaesthesia. Duration of infused sedation seems to have effect on psychomotor functions as longer operative procedures (> 30 minutes) had loss of recovery pattern. Subjects who had higher education and employed had better performance of cognitive tests but still slower recovery as compared to control group. Also the assessment of both the cognitive tests were done and MMSE was found to be more sensitive in detecting the cognitive changes as compared to SOMCT, while SOMCT was more specific.